Venturas y desventuras de la voluntad. Reflexiones a partir de la fenomenología de Edmund Husserl. (2014)
This research questions about the scope and limits of the volitional acts. From Husserl´s description of the structure and genesis of voluntary acts, the question arises about unaware determinations of the decisions and about the volitional resolutions. The phenomenological description of the will is primarily connected with the ethical considerations on the conditions for the realization of a full and happy life. However, Husserl´s phenomenology provides the basis for studying the will in general. While it is true that psychoanalysis does not provide a description of the will, it offers a description of its boundaries and the ability to understand the importance of failure as a way of moderating a proud will. Despite its restrictions and constraints, the will forms a part of human nature. The clarification of such limits and conditions of the will is an issue where the empirical investigations of psychoanalysis and those of transcendental phenomenology fruitfully coincide.